Reflections on Memorizing the Qur'an on the Spiritual Intelligence of Santri Ma'had Al-Mubarok Al-Islami Litahfidzil Qur'an Al-Karim - Noviyani, Dedek; Hayati, Elli Nur (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The purpose of this study was to describe the reflection of the effect of memorizing the Koran on the spiritual intelligence of students. This study uses a qualitative method with a phenomenological approach. The sampling technique used was purposive sampling, while data collection was carried out by observation and interviews. Then the data analysis process used thematic analysis (tradition) The results of this study indicate that memorizing the Koran affects the spiritual intelligence of the five subjects and of course there have been many changes from before and after memorizing the Koran to the spiritual intelligence of Ma'had Al-Mubarok students to make the students better in living their daily lives. The conclusion of this study is that the five subjects felt the impact of memorizing the Koran on their spiritual intelligence. There were supporting factors which influenced, namely pure intention because of Allah, and consistent worship (istiqomah) and the motivation of parents, teachers, and families. While the inhibiting factors are laziness and the temptation to use gadgets.Tujuan penelitian ini adalah untuk mengetahui refleksi pengaruh menghafal al-Quran terhadap kecerdasan spiritual santri. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Teknik pengambilan sampel yang di gunakan adalah purposive sampling, pengumpulan data dilakukan dengan observasi dan wawancara. Kemudian proses analisis data menggunakan tradisi analisis tematik (Thematic Analysis). Hasil dari penelitian menunjukkan bahwa refleksi kelima subjek menghafal al-Quran berpengaruh terhadap kecerdasan spiritual mereka. Banyak perubahan dari sebelum dan sesudah menghafal al-Quran terhadap kecerdasan spiritual santri Ma’had Al-Mubarok sehingga menjadikan santri lebih baik dalam menjalani kehidupan sehari-hari. Kesimpulan dari penelitian ini kelima subjek merasakan pengaruh dari menghafal al-Quran terhadap kecerdasan spiritual sehingga mengalami perubahan dari sebelum dan sesudah menghafal Quran. Ada dua faktor pendukung yang mempengaruhi yaitu niat semata karna Allah dan ibadah yang istiqomah, serta motivasi orang tua, guru dan keluarga. Sedangkan faktor penghambatnya adalah rasa malas dan godaan penggunaan gawai.